[Rezension von: James, David, Art, myth and society in Hegel's Aesthetics] - Peters, Julia (Bulletin of the Hegel Society of Great Britain, 2012)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0263523200000549/resource/name/firstPage-S0263523200000549a.jpg
Online veröffentlich am 22. April 2013
Gesehen am 01.12.2022
Keywords: Rezension